Economic constraints as drivers of coffee rust epidemics in Nicaragua - Villareyna, Rogelio.; Barrios, M.; Vílchez, Sergio; Cerda, Rolando; Vignola, Raffaele; Avelino, Jacques (Elsevier, Ámsterdam, Países Bajos, 2020)
Coffee rust (Hemileia vastatrix) epidemics of an intensity never seen before have hit Central America since 2012. This study set out to identify management and socio-economic factors that facilitate coffee rust development in Nicaragua and to learn how farmers perceive these epidemics. To that end, we conducted a series of interviews with farmers and carried out field observations a year after the peak of the 2012-13 epidemic. Twenty-nine pairs of plots (a pair was one heavily hit plot and another slightly hit plot in the same location) in the municipalities of Jinotega, Tuma-La Dalia and San Ramon were characterized for their management and coffee rust impact. This information was completed through interviews with the farmers. In addition, farmers provided their perception of the reasons for differences of coffee rust intensities between plots and information about their socio-economic situation. From multivariate analyses, we deduced that young coffee trees, timely applications of fungicides based on disease monitoring, shade pruning, and soil and foliar fertilizers seemed to be key practices in managing coffee rust. These practices were well known by the farmers, but socio-economic difficulties severely held back their application, as revealed by a mental model approach. Low coffee economic resources were particularly mentioned by farmers as a constraint to applying the practices needed to manage coffee rust. The highest coffee rust intensities and impacts were found in plots where the farmers, in general, had no education, no training, a low number of direct technical advices, and low incomes. To our knowledge, this is the first time that poor economic conditions have been related to the development of intense plant disease outbreaks. These relationships indicated that technical solutions to manage coffee rust are not sufficient and that economic solutions, where the market has a crucial role to play, need to be implemented.